2017
DOI: 10.7759/cureus.1183
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Inflammatory Myofibroblastic Tumor in Lung and Brain: A Case Report and Review of Literature

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare entity and a diagnostic challenge with myriad clinical presentations and pathogenetic mechanisms. Isolated occurrences can be at any site in the body; however, only a few cases of IMT with the concomitant appearance of different organs have been published. We report a unique occurrence of bilateral inflammatory myofibroblastic tumor of the lungs with synchronous brain parenchymal lesions in an 11-year-old male, detailing clinical presentation with the emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…suggested that patients with IMT in the lungs should be screened for brain lesions even if asymptomatic. [ 20 ] In our study, 12.5% of cases with follow-up data developed brain metastasis. Very rarely, IMT may show sarcomatous transformation, as in one patient of our study [ Figure 8 ].…”
Section: Discussionmentioning
confidence: 51%
“…suggested that patients with IMT in the lungs should be screened for brain lesions even if asymptomatic. [ 20 ] In our study, 12.5% of cases with follow-up data developed brain metastasis. Very rarely, IMT may show sarcomatous transformation, as in one patient of our study [ Figure 8 ].…”
Section: Discussionmentioning
confidence: 51%
“…Rare cases of the coexistence of pulmonary and brain IMTs have been reported, where it was not clear whether the brain lesion was metastatic or part of multifocal disease [10]. Jehangir et al suggested that patients with IMT in the lungs should be screened for brain metastasis even if asymptomatic [10]. Our patient developed a rapid local recurrence, followed by spinal and brain metastasis within a short interval of six to eight months.…”
Section: Discussionmentioning
confidence: 66%
“…In a study by Irodi et al,12.5% of cases of thoracic IMT developed brain metastasis on follow-up [9]. Rare cases of the coexistence of pulmonary and brain IMTs have been reported, where it was not clear whether the brain lesion was metastatic or part of multifocal disease [10]. Jehangir et al suggested that patients with IMT in the lungs should be screened for brain metastasis even if asymptomatic [10].…”
Section: Discussionmentioning
confidence: 99%
“…They usually involve cutaneous and subcutaneous tissues [1] . Less common locations include bones and internal organs: lung, heart, gastrointestinal tract, and central nervous system [5] , [6] , [7] , [8] .…”
Section: Discussionmentioning
confidence: 99%